English Camp: English For Hospitality In Offical Meeting - Nelly Astuti Hasibuan; Putri Ramadhani; Soeb Aripin (JPM: Jurnal Pengabdian Masyarakat, 2022)
Dagang Kerawan Village, located in Tanjung Morawa District, Deli Serdang Regency, has various Small and Medium Enterprises (SMEs) whose products have been marketed to the public. Products produced by Small and Medium Enterprises (SMEs) from the people of Dagang Kerawan Village actually have the potential to be marketed overseas. One of the competencies needed to market SME products to various countries is the ability to communicate in English. The English Camp activity will deliver special materials that will help village officials and the UKM village community to welcome and communicate with guests who come from abroad. The material will be packaged in the form of Coversation (Conversation) to make it easier for participants to understand. With this activity, it is hoped that the village community will begin to realize the importance of having the ability to speak English.